CONSTRUCTION OF LEGAL PROTECTION FOR CONSUMERS AGAINST THE MISUSE OF DEEPFAKES IN ADVERTISING SOCIAL MEDIA - Dewi Nur Hidayah; Ubaidillah Kamal (Law Research Review Quarterly, 2026)
Deepfakes, which utilize artificial intelligence to produce hyper-realistic audiovisual content in social media advertisements, are increasingly being misused by irresponsible businesses, who are exploiting deepfake technology to create advertising content. This study aims to identify existing regulatory frameworks in Indonesia and consumer legal protection against the misuse of deepfake technology, and to provide recommendations for strengthening the legal system to combat content manipulation by deepfake abuse. This study employs a normative juridical method, employing a statute approach. The data used in this study include both primary and secondary legal materials, including relevant regulations and related literature. The data collection technique used a literature study. The results of the study indicate a legal vacuum and significant difficulties in detecting and proving deepfake violations in social media advertisements. Although regulations exist, the misuse of deepfake technology is not yet explicitly regulated, so legal protection for consumers is not optimal. Consumer legal protection can be provided through two approaches: preventive legal protection and repressive legal protection. The increasingly sophisticated development of AI also increases the risk of misuse that harms consumers and society, necessitating adaptive legal responses to ensure more effective protection in this era of technological advancement. This research is expected to serve as a reference for regulators in developing strategic steps to address the threat of deepfakes.